Mixture of Organophosphates Chronic Exposure and Pancreatic Dysregulations in Two Different Population Samples - Leonel Javeres, Mbah Ntepe; Raza, Saqlain; Judith, Ngondi; Anwar, Fozia; Habib, Rabia; Batool, Sajida; Nurulain, Syed Muhammed (Frontiers in Public Health, 2020)
Organophosphates (OPs) constitute a major agrochemical. The application of OP pesticides is expected to increase multifold in coming decades. The etiology of diabetic diseases is attributed to multiple factors including OP pesticides exposure. The present study investigates the pancreatic dysregulation with respect to exocrine enzymes and diabesity in the groups of Pakistani and Cameroonian population exposed to mixture of OP pesticides. Nine hundred and four OPs exposed individuals were enrolled for this cross-sectional type of study after due consent and approval from ethical review committee. Pesticides residues were measured by GC-MS spectrometry. Cholinergic enzymes were measured by Elman’s method. Serum glucose, insulin, serum amylase, lipase, and triglyceride were measured by spectrophotometry and ELISA respectively; HOMA-IR was determined in OPs exposed and non-exposed participants. Stata 15 and R 3.2.0 software were used for statistical analysis of the data. Malathion, chlorpyrifos and parathion residues were evident in plasma samples. RBC-acetylcholinesterase was significantly depressed in OPs exposed groups. In both population samples, investigated pancreatic functions were found to be statistically significantly dysregulated than non-exposed. OPs exposure indicated risk of diabetes and insulin, glycaemia, adiponectin, triglycerides and TNF-α dysregulations. The study concludes that both OPs exposed population groups exhibited mixture of OPs residues and pancreatic dysregulation albeit effect was more pronounced in Cameroonian population. In addition, serum lipase has positive correlation with OPs exposure and diabetes and may be suggested as an alternate/additional diagnostic marker for diabesity under OPs exposure. However, screening of other environmental co-factors with OPs for pancreatic dysregulation is suggested.